Study of phase transformation and surface microstructure of alumina ceramic under irradiation of intense pulsed ion beam - Zhang, Shijian; Yu, Xiao; Zhang, Jie; Shen, Jie; Zhong, Haowen; Liang, Guoying; Xu, Mofei; Zhang, Nan; Ren, Jianhui; Kuang, Shicheng; Shang, Xuying; Adegboyega, Oluwasogo; et al. (Vacuum, 2021)
Intense pulsed ion beam (IPIB), featured with pulsed high-power density, has been widely used in the modification of structural material, especially in high strength materials. The effects of IPIB treatment on phase transformation and surface microstructure of alumina ceramics were investigated in this work. Experiments were carried out on the BIPPAB-450 accelerator with peak accelerating voltage and current density of 360 kV and 170 A/cm2. X-ray diffraction (XRD), scanning electron microscope (SEM) and atomic force microscope (AFM) were used to analyze the phase transformation and cross-section and surface morphology of alumina ceramics under IPIB treatment. The XRD pattern indicated that phase transformation from α-Al2O3 to γ-Al2O3 occurred on the irradiated area due to the combined effect of rapid re-solidification and thermal stress caused by IPIB. The SEM cross-section images indicated that homogeneous modified layer with thickness up to 1.53 μm was produced and cracks inside sample were observed as well after IPIB irradiation. The evolution of cracks on surface of samples with pulse number was investigated in this work. Micro-holes distributed on the net structure of cracks were observed after IPIB irradiation and the evolution of size and number of micro-holes with pulse number was discussed. •Phase transformation from α-Al2O3 to γ-Al2O3 was confirmed by XRD after irradiation of intense pulsed ion beam.•The relationship between the evolution of micro-holes caused by IPIB and pulse number was investigated.•The roughness of surface decreased to minimum after 1 pulse irradiation of IPIB.